Dexamethasone reduces vascular endothelial growth factor in comparison to placebo in post-operative chronic subdural hematoma samples: A target for future drug therapy? - Edlmann, Ellie; Giorgi-Coll, Susan; Thelin, Eric P.; Hutchinson, Peter J.; Carpenter, Keri L. H. (Frontiers in Neurology, 2022)
Background Chronic subdural hematoma (CSDH) is a collection of blood and fluid that arises on the brain surface due to a combination of trauma and/or inflammation. The mainstay of treatment is surgical drainage, but CSDH can recur. Dexamethasone has been shown to reduce CSDH recurrence, but its mechanism of action has not been fully elucidated. Understanding the inflammatory mediators driving CSDH formation and recurrence and how dexamethasone alters this can help develop new therapeutic strategies. Methods A subgroup of adult patients recruited to the Dex-CSDH trial, randomized to dexamethasone or placebo, who had surgery for their CSDH, were included. CSDH fluid and peripheral blood were collected intraoperatively, from post-operative drains and operated recurrences. Samples were analyzed using a 12-plex panel of inflammatory mediators. Clinical patient data were also reviewed. Results A total of 52 patients, with a mean age of 76 years, were included. Five recurrent CSDHs occurred. Vascular endothelial growth factor (VEGF) had the highest concentration across all CSDHs, and only matrix metalloproteinase (MMP)-9 had lower concentrations in CSDH compared to plasma but was increased in recurrent CSDHs. The interleukin (IL)-10 concentration was significantly lower in primary CSDHs that recurred. Most inflammatory mediators increased post-operatively, and dexamethasone significantly reduced the post-operative peak in VEGF on day 2, compared to placebo. Conclusion It is evident that VEGF plays a critical role in the inflammatory response in CSDH. The post-operative reduction with dexamethasone could signal the mechanism by which it reduces recurrence. Novel therapies with a better side-effect profile than dexamethasone should be targeted at VEGF or potential alternatives such as IL-10 supplementation.